"If I can get over that, I can get over anything"—understanding how individuals with acute whiplash disorders form beliefs about pain and recovery: a qualitative study. Issue 2 (June 2015) - Williamson, Esther; Nichols, Vivien; Lamb, Sarah E.
Abstract: Objectives: Beliefs held by patients have been shown to influence outcomes in acute whiplash associated disorders (WAD). The aim was to identify beliefs about pain and recovery present in the narratives of individuals with WAD and to understand how and why individuals' came to hold these beliefs. Design: A qualitative study. Interpretative Phenomenological Analysis of semi-structured interviews. Participants: Participants ( n = 20) were enrolled in a large, pragmatic randomised controlled trial of physiotherapy for acute WAD. Participants were interviewed after they completed their treatment. Results: A range of beliefs were evident. These included beliefs about exercise and activity, ability to self-manage symptoms, expectations of recovery and competing priorities. Some beliefs appeared to be barriers to recovery despite all participants having consulted several health professionals. Health professionals were highly influential over how individuals' thought about and managed their injury. The pain experienced influenced how individuals thought and behaved as did past experiences of injury and illness. Competing priorities were a potential barrier to engaging with treatment. We identified examples of how beliefs and behaviour changed in response to information from health professionals and the pain they experienced. Conclusion: People with WAD hold a range of beliefs about pain and recovery and some appear unhelpful to recovery. Health professionals can influence these beliefs and encourage behaviours that aid recovery. Understanding how patients form beliefs may help health professionals to address unhelpful beliefs. It is important that advice and education provided is in line with the current evidenced based understanding of pain and recovery.